PENGARUH PUPUK KOTORAN AYAM DAN BIOCAR ARANG SEKAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KANGKUNG DARAT (Ipomea reptans Poir) PADA MEDIA TANAH MASAM: THE EFFECT OF CHICKEN MANURE AND BIOCAR FERTILIZER ON THE GROWTH AND YIELD OF LAND SWEET SPINACH (Ipomea Reptans Poir) ON ACID SOIL - Nadiah; Firnia, Dewi; Rusmana; Rohmawati, Imas (Fakultas Pertanian Universitas Palangka Raya, 2024)
Acid soil status can affect the physical, chemical and biological properties of the soil which have an impact on plant growth, nutrient availability and damage microbial activity in the soil. This research aims to determine the response of land kale plants to the application of doses of chicken manure fertilizer and husk charcoal biochar on acid soil media. The study used a randomized block design (RCBD) with 2 factors. Chicken manure as the first factor with dosage levels, namely 0 t ha-1, 20 t ha-1, 40 t ha-1, and 60 t ha-1. The dosage of husk charcoal biochar as factor 2 is 0 t ha-1, 15 t ha-1, and 30 t ha-1. The results of the research showed that the treatment of chicken manure fertilizer with husk charcoal biochar had a very significantly different effect on the parameters of plant height and number of leaves at 21 and 28 DAP. From the research that has been carried out, chicken manure and husk charcoal biochar have an interaction on the leaf number parameter at 21 DAP